(IN)EXISTENCE OF INFLATION REVIEW OF THE BASIS OF EXEMPTION AND APPLICATION OF INDIVIDUAL INCOME TAX RATES (REMUNOM, 2023)
The Brazilian legislation that governs the personal income tax (IRPF), a tax under the jurisdiction of the Union, has serious flaws regarding the classification and updating of exemption ceilings and the application of their rates, which causes fiscal injustice to thousands of Brazilian citizens, increasing the disparity in the tax burden between the upper, middle and poor classes. In the middle of this year, 2023, Law No. 14,663/2023 was approved and sanctioned by the President of the Republic, which changed the values ​​of the monthly table of said tax. Furthermore, the simple modification does not resolve the core of the legal imbroglio that exists in the regarding the lack of constant updating of the IRPF table. For its construction, the methodological procedure was anchored in bibliographical research, of an analytical-exploratory nature, carried out on legislation, doctrines and articles related to the topic. Therefore, it was concluded that, despite the recent update carried out by Law no. 14,663/2023 is highly appreciated, the lack of constant inflationary review of the IRPF causes a series of harms, such as the growth of tax injustice, and the definitive solution would only occur with the solidification of the mandatory inflationary update of the exemption range and IRPF table in the Federal Constitution of 1988.